2016
DOI: 10.1038/srep37960
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cell behavior on pva/pva-gelatin electrospun nanofibers with random and aligned configuration

Abstract: Electrospinning technique is able to create nanofibers with specific orientation. Poly(vinyl alcohol) (PVA) have good mechanical stability but poor cell adhesion property due to the low affinity of protein. In this paper, extracellular matrix, gelatin is incorporated into PVA solution to form electrospun PVA-gelatin nanofibers membrane. Both randomly oriented and aligned nanofibers are used to investigate the topography-induced behavior of fibroblasts. Surface morphology of the fibers is studied by optical mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(77 citation statements)
references
References 20 publications
(21 reference statements)
2
72
0
1
Order By: Relevance
“…Cell organisation on cryogenic scaffold acted similarly to aligned scaffolds in that cells attached themselves along individual fibres. These results are analogous to those presented by Huang et al (2016) who showed an increased interaction of cells with PVA-gelatin scaffolds compared to PVA alone where spreading of cells suggests good adhesion between ECM proteins and scaffold. This cell spreading on plasma treated electrospun PCL scaffolds is beneficial to groups studying the effect of external mechanical stimulus on cells, especially in the case of aligned scaffolds.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Cell organisation on cryogenic scaffold acted similarly to aligned scaffolds in that cells attached themselves along individual fibres. These results are analogous to those presented by Huang et al (2016) who showed an increased interaction of cells with PVA-gelatin scaffolds compared to PVA alone where spreading of cells suggests good adhesion between ECM proteins and scaffold. This cell spreading on plasma treated electrospun PCL scaffolds is beneficial to groups studying the effect of external mechanical stimulus on cells, especially in the case of aligned scaffolds.…”
Section: Discussionsupporting
confidence: 78%
“…We have seen distinct morphological differences in cells grown on different architectures, similar to other findings (Yan et al 2012;Mahjour et al 2016;Huang et al 2016). Our random scaffolds show cells in a more rounded morphology, spread between numerous fibres.…”
Section: Discussionsupporting
confidence: 76%
“…However, the add it ion of PVA seems to create some regular globs with various sizes caused by different rat ios of PVA [14]. Th is results may be attributed to the non-adhesive property of PVA, wh ich restricts the adhesion and spread o f the CM C [15].…”
Section: Resultsmentioning
confidence: 99%
“…The absorption peaks appeared at ∼1640 and ∼1400 cm −1 is most probably, either due to C=C and C-C stretching, respectively, or from the symmetric and asymmetric stretching vibration of the C=O/C-O group. The absorption peaks appeared at ∼3000 cm −1 is due to the symmetric and asymmetric stretching vibration of CH 2 [29,30]. The absorption bands appeared at ∼1300 and ∼940 cm −1 was ascribed to symmetric C-H and bending vibration of -CH 3 group, respectively.…”
Section: Ft-ir Analysismentioning
confidence: 95%